PROFIL PENGENDALIAN DIABETES MELITUS TIPE 2 DI POLIKLINIK PENYAKIT DALAM RUMAH SAKIT UMUM CUT MUTIA KABUPATEN ACEH UTARA - Fakhrul Rizal; Mohammad Hendro Mustaqim (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Diabetes mellitus is a metabolic disease characterized by an increase in blood sugar levels or hyperglycemia that occurs when the pancreas is unable to produce enough insulin for the body, an abnormality in insulin secretion occurs or the body is ineffective in using this insulin. According to WHO, diabetes sufferers continue to increase every year until it reaches figure 415 million people. The 2018 RISKESDAS shows that in Aceh there was an increase in cases from 2013 to 2018 by 2.0%. The purpose of this study was to determine the control profile of physical activity, diet, and medication adherence to type 2 diabetes mellitus sufferers. The sample in this study amounted to 100 people with a total sampling technique. The design of this research is descriptive observational with cross sectional approach. The results showed that out of 100 respondents who suffered from type 2 diabetes mellitus, according to the adherence to taking medication, 54 people (54%) were in the moderate category and 3 people (3%) were in the high category. Based on physical activity, 49 people (49%) had light activities and 15 people (15%) had heavy activities. Based on the diet, 100 people (100%) are in the good category. The recommendation of this study is expected to be an input for hospitals to provide data books for new and old patients for cases of type 2 diabetes mellitus.Keywords:Â type 2 diabetes mellitus profile, physical activity, based on the diet, adherence to taking medication